Woodburning project & pattern treasury - Pompano, Deborah (East Petersburg, PA : Fox Chapel Pub., 2011)
" From the simple beauty of a single oak leaf to an elaborate portrait of nature - the patterns of woodburning artist, Deborah Pompano are beyond compare. Inside this, her first book, Pompano shares techniques for getting started in woodburning. You'll learn what 5 tips she recommends, how to create a vast variety of dimension, shade and texture with your woodburner and how to develop your drawing skills for use in pyrography. At the heart of this book is an unbelievable treasure trove of patterns. In this section, you will find individual elements, border patterns, and central images which can be mixed-and- matched to create personal works of art. Or, you can refer to one of the authors complete composition patterns which weave poems and verse with imagery from the natural world to create inspirational woodburnings. The patterns cover a wide spectrum of themes including: harvest, arbor, birds and other wildlife, seaside, clipper ship, teatime, Native American, garden, floral, lighthouse, and much more. The book includes two practice exercises, one step-by-step project and close-up instruction on lettering. "--
Includes index.
Machine generated contents note: Introduction Chapter 1: Getting Started *Tools and Materials *Setting up your workspace *Design Chapter 2: Practice Projects *Drawing exercises *Burning exercises Chapter 3: Step-by-Step Projects Chapter 4: Patterns Chapter 5: Gallery.
Keywords: Pyrography; Pattern books